Fundamentals of Geobiology - Knoll, Andrew H.; Konhauser, Kurt O.; Canfield , Donald E.; Canfield, Donald E. (West Sessex : Wiley-Blackwell, 2012)
This book is the first to set out a coherent set of principles that underpin geobiology, and will act as a foundational text that will speed the dissemination of those principles. The chapters have been carefully chosen to provide intellectually rich but concise summaries of key topics, and each has been written by one or more of the leading scientists in that field.. Fundamentals of Geobiology is aimed at advanced undergraduates and graduates in the Earth and biological sciences, and to the growing number of scientists worldwide who have an interest in this burgeoning new discipline.
Includes bibliographical references.; Index 437-443p.
Keywords: Geology; Palaeoecology; Palaeogeography; Geobiology